Depression in Osteoporosis and Effects on Quality of Life - Şule Şahin Onat; Sibel Ünsal Delialioğlu; Seda Biçer; Sumru Özel (Türk Osteoporoz Dergisi, 2013)
Objective: The aim of this study was to identify risk factors for the development of depression in patients with osteoporosis, and to measure the psychosocial effects to the change in quality of life. Material and Methods: 125 patients with osteoporosis were included in the study. A questionnaire was completed which was including age, sex, marital status, education level, occupation, height, weight, alcohol use, smoking, physical activity level, milk consumption, previous fragility fracture of the patients. Bone mineral density of the lumbar spine and femoral neck were measured with DEXA. Back and lumbar compression fractures of the individuals were recorded by back and lumbar radiography. To evaluate back pain, Visual Analog Scale (VAS) was used. To assess depression in patients, Beck Depression Inventory (BDI) was used, and to assess the quality of life the European Council of Osteoporosis Quality of Life Questionnaire (QUALEFFO) was used. Results: 125 patients were included in the study, 57 patients (45.6%) had depression and 68 patients (54.4%) had not depression. The average age, illiteracy status, reduced physical activity level were higher in the patients with depression than the patients without depression. Vertebral compression fracture, family history of fracture, fall predisposition, and osteopenia in the risk factors of osteoporosis were found statistically significantly higher in the group with depression than the group without depression. Both lumbar and femoral T and Z values, and VAS values were significantly higher in the patients with depression than the patients without depression (p<0.05). The total value and all sub-parameters of quality of life scale QUALEFFO were significantly higher in patients with depression than patients without depression (p<0.05). Positive significant correlation was found between BDI scores and sub-parameters of QUALEFFO scores (p<0.05). Conclusion: Depression in individuals with increased bone loss was shown to lead to a further decrease in the quality of life. (Turkish Journal of Osteoporosis 2013;19: 58-64)